LITHOSPHERIC THICKNESS BENEATH THE DABIE SHAN, CENTRAL EASTERN CHINA FROM S RECEIVER FUNCTIONS - Sodoudi F.; Yuan X.; Kind R.; Liu Q.; Chen J. (My University, 2006)
P and S receiver functions obtained from a portable array of 34 broad-band stations in east central China provide a detailed image of the crust-mantle and lithosphere-asthenosphere boundaries (LAB) in the Dabie Shan and its adjacent areas. Clear S-to-P converted waves produced at the LAB show a thin lithosphere beneath the whole study area. Based on our results, the thickest lithosphere of 72 km is observed beneath the southern part of the area within the Yangtze craton, whereas beneath the North-China platform, the lithosphere is only 60 km thick. S receiver functions also reveal, in good agreement with P receiver functions, a maximum depth of the Moho beneath the Dabie Shan orogen at approximately 40 km. Furthermore, we interpret the structural difference at 32° latitude as the probable location of the mantle suture formed between the Yangtze and the Sino-Korean cratons. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ASTHENOSPHERE; CRUST; LITHOSPHERE; MANTLE; S RECEIVER FUNCTION